Analysis of Evaluation of Revegetation Plant Growth on Post-Mining Land as an Effort to Restore the Function of Absorbing Carbon Dioxide Emissions - Yuniar Pratiwi; Reni Arisanti; Gilang Sagita (Jurnal Ilmu Lingkungan, 2025)
Mining activities can reduce carbon dioxide emissions by opening mining areas, so efforts are needed to restore land function through reclamation and revegetation. Increasing vegetated land can help mitigate climate change. This study aims to evaluate the growth of revegetation plants to determine the success of revegetation. The study was conducted on post-mining land by observing several types of revegetation plants. Observed parameters included height, stem diameter, number of plants, plant survival rate and carbon absorption. Data were analyzed using a descriptive approach. The results showed that the revegetation success rate on ex-mining land at PT X reached 93%, with plant growth at 93.7%, plant health at 92.3%, and a plant density of 590 plants/ha. The resulting carbon absorption was 10.12 tons. High revegetation success can increase oxygen production and carbon dioxide absorption, thereby restoring the environmental functions of vegetated land. In addition, changes in land cover directly affect carbon storage.